What Will Be Already Exists : Temporalities of Cold War Archives in East-Central Europe and Beyond - Kürti, Emese; László, Zsuzsa (2021)
How do artist archives survive and stay authentic in radically changed contexts? The volume addresses the challenge of continuity, sustainability, and institutionalization of archives established by Eastern European artists. At its center stands the 40th anniversary of the Artpool Art Research Center founded in 1979 in Budapest as an underground institution based on György Galántai's »Active Archive« concept. Ten internationally renowned scholars propose contemporary interpretations of this concept and frame artist archives not as mere sources of art history but as models of self-historicization. The contributions give knowledgeable insights into the transition of Cold War art networks and institutional landscapes.